Does protein unfolding play a functional role in vivo?. (1st September 2020) - Sharma, Sabita; Subramani, Smrithika; Popa, Ionel
Abstract : Unfolding and refolding of multidomain proteins under force have yet to be recognized as a major mechanism of function for proteins in vivo . In this review, we discuss the inherent properties of multidomain proteins under a force vector from a structural and functional perspective. We then characterize three main systems where multidomain proteins could play major roles through mechanical unfolding: muscular contraction, cellular mechanotransduction, and bacterial adhesion. We analyze how key multidomain proteins for each system can produce a gain‐of‐function from the perspective of a fine‐tuned quantized response, a molecular battery, delivery of mechanical work through refolding, elasticity tuning, protection and exposure of cryptic sites, and binding‐induced mechanical changes. Understanding how mechanical unfolding and refolding affect function will have important implications in designing mechano‐active drugs against conditions such as muscular dystrophy, cancer, or novel antibiotics. Abstract : How mechanical unfolding of proteins has a functional role in vivo is still poorly understood. In this review, we distill the main biophysical characteristics of multidomain proteins functioning under force as binary molecular computational units and examine them as part of several biological processes. Understanding the relation between molecular unfolding of proteins under force and their overall macroscopic impact can provide insight into novel mechanical signaling pathways and gain‐of‐function mechanisms.